Sex-Related Differential Whole-Brain Input Atlas of Locus Coeruleus Noradrenaline Neurons - Sun, Pei; Wang, Junjun; Zhang, Meng; Duan, Xinxin; Wei, Yunfei; Xu, Fuqiang; Ma, Yan; Zhang, Yu-Hui (Frontiers in Neural Circuits, 2020)
As the most important organ in our bodies, brain plays critical roles in deciding the sex-related differential features; however, the underlying neural circuitry basis remains unclear. Here, we used cell-type-specific rabies virus-mediated monosynaptic tracing systems to generate sex differences-related whole-brain input atlas of locus coeruleus noradrenaline (LC-NE) neurons. We developed custom pipelines for brain-wide comparisons of input sources in both sexes with the registration of the whole-brain data set to the Allen Mouse Brain Reference Atlas. Among 257 distinct anatomical regions, we demonstrated the differential proportions of inputs to LC-NE neurons in male and female mice at different levels. LC-NE neurons of two sexes showed general similarity in the input patterns, but with differentiated input proportions quantitatively from major brain regions and diverse sub-regions. For instance, inputs to male LC-NE neurons were dominated in cerebrum, interbrain and cerebellum, whereas inputs to female LC-NE neurons were dominated in midbrain and hindbrain. We further found that specific subsets of nuclei nested within sub-regions contributed to overall sex-related differences in input circuitry. Furthermore, among totaled 123 anatomical regions with proportion of inputs > 0.1%, we also identified 11 sub-regions with significant statistical differences of total inputs between male and female mice, and 7 of them also showed such differences in ipsilateral hemispheres. Our study not only provides a structural basis to facilitate our understanding of sex differences at circuitry level but also provides clues for future sexually differentiated functional studies related to LC-NE neurons.